2003
DOI: 10.1002/cncr.11230
|View full text |Cite
|
Sign up to set email alerts
|

Molecular markers of outcome after radiotherapy in patients with prostate carcinoma

Abstract: Gekippt oder nicht gekippt: Die Kristallstruktur von P3HT (Phase I) wurde mit einer Kombination aus Röntgenbeugung, Festkörper‐NMR‐Spektroskopie und DFT‐Rechnungen bestimmt. Die Ergebnisse zeigen, dass das halbleitende Polymer in der monoklinen Raumgruppe P21/c mit nicht‐gekippten π‐Stapeln im Abstand von 3.9 Å kristallisiert (siehe Bild).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
70
0
2

Year Published

2003
2003
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 96 publications
(72 citation statements)
references
References 46 publications
(77 reference statements)
0
70
0
2
Order By: Relevance
“…Clinical studies have shown that bcl-2 overexpression, and/or abnormal bax expression, is associated with an increased risk of biochemical failure after radiotherapy (12,13,23). Moreover, Bcl-2 is overexpressed in recurrent tumors after RT (24,25).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical studies have shown that bcl-2 overexpression, and/or abnormal bax expression, is associated with an increased risk of biochemical failure after radiotherapy (12,13,23). Moreover, Bcl-2 is overexpressed in recurrent tumors after RT (24,25).…”
Section: Discussionmentioning
confidence: 99%
“…In prostate cancer, overexpression of bcl-2 is associated with prostate tumor aggressiveness (7)(8)(9). Moreover, Bcl-2 protein is increased in the majority of tumors from men with androgen-refractory disease and is associated with resistance to androgen deprivation and RT (4,6,(10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…Abnormal bax expression in our study was classified as overexpression or underexpression based on the results of a prior report (7). The initial rationale for this subdivision was that bax overexpression would be favorable in the setting of radiation due to the promotion of apoptosis, while its underexpression should lead to less of a response to radiation.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have established that bcl-2 can protect against cell death resulting from genotoxic stress in general and p53 activation specifically Adams and Cory, 1998;Schumacher et al, 2001). Additionally, recent findings suggest that bcl-2 levels in tumor cells may provide important predictive information in cancer patients (Mano et al, 1999;Pollack et al, 2003). Understanding the clinically relevant molecular variables that are likely to influence p53 function, including upregulation of the anti-apoptotic bcl-2 oncoprotein, will facilitate the ultimate success of these trials.…”
Section: Discussionmentioning
confidence: 99%